Method for preparing ferrous sulfate from hematite slag
By using SO2 reduction and leaching technology to treat hematite slag in the wet zinc smelting industry, the problem of high cost and low purity of preparation of ferrous sulfate in the existing technology is solved, and efficient and low-cost preparation of ferrous sulfate is achieved, expanding the Resource utilization of hematite slag.
Patent Information
- Application Number
- CN202411693393.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
AI Technical Summary
The existing methods for preparing ferrous sulfate from hematite slag have problems of high cost and low purity.
The SO2 reduction leaching technology is used to treat hematite slag produced in the wet zinc smelting industry, and ferrous sulfate is obtained by reacting with concentrated sulfuric acid and SO2. The method includes reacting the hematite slag with concentrated sulfuric acid and SO2 in a closed container to obtain the hematite residue and the SO2 reduction leaching solution, and then undergoing crystallization treatment to obtain high-purity ferrous sulfate.
The cost of preparing ferrous sulfate is reduced, the purity of the product is improved, the utilization of hematite slag is expanded, and the resource utilization of iron is realized.
Smart Images

Figure BDA0005151548820000091 
Figure HDA0005151548830000011
Abstract
Description
Technical Field
[0001] The present application belongs to the field of solid waste resource utilization, and specifically relates to a method for preparing ferrous sulfate using hematite slag. Background Art
[0002] At present, most of the zinc in the world is produced by roasting-leaching-electrodeposition process. After the traditional neutral leaching-low acid leaching, a considerable part of the zinc still exists in the zinc leaching slag in the form of ferrite. In order to improve the recovery rate of zinc, the zinc leaching slag is usually treated by pyrometallurgical process or hydrometallurgical process. The pyrometallurgical process for zinc leaching slag has a high zinc recovery rate, but there is a problem of low recovery rate of associated high-melting-point metals; the hydrometallurgical process has a high metal recovery rate, but the iron in the system needs to be removed to ensure the smooth operation of the system. The current iron removal methods include goethite method, jarosite method, and hematite method. Among them, the goethite method and jarosite method have low iron content, large slag volume and belong to hazardous waste and need to be properly disposed of, while the hematite slag produced by the hematite method has the advantages of high iron content and small slag volume, which can be used as raw materials for the steel industry and cement industry, realizing the resource utilization of iron in the hydrometallurgical zinc smelting system.
[0003] Ferrous sulfate is called "green vitriol" and is widely used in agriculture, industry, animal husbandry, battery electrodes and other fields. It is currently mainly obtained through the waste iron sulfuric acid method, titanium dioxide by-product method, and pyrite slag preparation method. At present, the source of ferrous sulfate in my country is mainly as a by-product of titanium dioxide. In addition, the industry has studied the use of other iron-containing wastes to prepare ferrous sulfate. The existing method of preparing ferrous sulfate from hematite slag has the problems of high cost and low purity. Therefore, the preparation technology of ferrous sulfate still needs to be further improved. Summary of the invention
[0004] This application is based on the inventor's discovery and understanding of the following facts and problems:
[0005] Compared with the original hematite slag and the iron-containing waste slag from non-ferrous smelting, the hematite slag produced in the process of hydrometallurgy has lower impurities and less soluble impurities, so it is easy to obtain ferrous sulfate solution with lower impurity content and its finished products. SO2 has a certain reducing property and can be used as Fe 3+ In the process of hydrometallurgical zinc production, a large amount of cheap and easily available SO2-containing flue gas is often produced, so SO2 is an ideal reducing agent. Compared with iron powder reduction, SO2 is used to reduce Fe 3+ The cost is lower.
[0006] In summary, the inventors have proposed a method for preparing ferrous sulfate by treating hematite slag produced in the hydrometallurgical zinc smelting industry using SO2 reduction leaching technology.
[0007] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application proposes a method for preparing ferrous sulfate from hematite slag with lower cost or higher product purity.
[0008] The present application proposes a method for preparing ferrous sulfate using hematite slag, comprising:
[0009] contacting a mixture containing hematite slag and concentrated sulfuric acid with SO2 in a first sealed pressure-resistant container for a first reaction to obtain hematite residue and SO2 reduction leaching solution;
[0010] The SO2 reduction leaching solution is subjected to a first crystallization to obtain a first solid product containing ferrous sulfate and a first post-crystallization liquid.
[0011] The use of the above method to prepare ferrous sulfate from hematite slag changes the current situation that hematite slag can only be used as raw material for ironmaking and cement, expands the utilization of hematite slag, and increases the added value of hematite slag.
[0012] In some embodiments, the mixture includes hematite slag, concentrated sulfuric acid and the first post-crystallization liquid, so that the first post-crystallization liquid can be recycled to improve the utilization rate.
[0013] In some embodiments, the hematite slag is hematite slag produced by removing iron by hematite method in hydrometallurgy, and the mass fraction of iron is greater than 55% based on the total mass of the hematite slag. It is thus easy to obtain ferrous sulfate solution with lower impurity content and its finished product, and the resource utilization of iron in the hydrometallurgy system can be realized.
[0014] In some embodiments, the SO2 is SO2-containing flue gas generated in a hydrometallurgical zinc smelting process, and the mass concentration of the SO2 exceeds 90%, thereby reducing the reduction cost.
[0015] In some embodiments, in the first sealed pressure-resistant container, the SO2 partial pressure is 0.15MPa to 0.2MPa, the first reaction time is 2h to 3h, and the first reaction temperature is 80°C to 90°C. This can make the reaction more complete and is conducive to the Fe 3+ Reduction to Fe 2+ .
[0016] In some embodiments, the total iron concentration in the SO2 reduction leaching solution does not exceed 140 g / L, which is conducive to ensuring the subsequent sedimentation separation.
[0017] In some embodiments, the first crystallization comprises: cooling the SO2 reduction leaching solution to 20°C to 30°C, stirring and cooling for 3h to 6h, and centrifuging, thereby promoting crystallization and improving efficiency.
[0018] In some embodiments, the method for preparing ferrous sulfate using hematite slag further comprises:
[0019] dissolving the first solid product to obtain a first solution;
[0020] contacting the first solution with H2S in a second sealed pressure-resistant container to perform a second reaction to obtain a pre-crystallization solution;
[0021] The pre-crystallization liquid is subjected to a second crystallization to obtain a second solid product containing ferrous sulfate and a second post-crystallization liquid.
[0022] The above-mentioned crude crystallization-redissolution-H2S reduction method eliminates the reduction of Fe by SO2. 3+ The incompleteness causes the low quality of ferrous sulfate, and in the process heavy metal impurities are separated, thus improving the product quality.
[0023] In some embodiments, the total iron concentration in the solution containing the first solid product is 130 g / L to 140 g / L, Fe 3+ The concentration is 1g / L~2.5g / L.
[0024] In some embodiments, the solution containing the first solid product includes the first solid product and the second post-crystallization liquid, thereby allowing the second post-crystallization liquid to be recycled and improved in utilization rate.
[0025] In some embodiments, in the second sealed pressure-resistant container, the H2S partial pressure is 0.01 MPa to 0.05 MPa, the second reaction time is 0.5 h to 1 h, and the second reaction temperature is 70° C. to 75° C. This is conducive to the reduction of Fe 3+ and precipitate heavy metals.
[0026] In some embodiments, the second crystallization comprises: cooling the pre-crystallization solution to 20° C. to 30° C., stirring and cooling for 3 h to 6 h, and centrifuging, thereby promoting crystallization and improving reaction efficiency.
[0027] In some embodiments, the second solid product may also be dried under vacuum conditions or under the protection of a nitrogen atmosphere, wherein the drying temperature does not exceed 40°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a process flow chart for preparing ferrous sulfate using hematite slag in an embodiment of the present application. DETAILED DESCRIPTION
[0029] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0030] The present application proposes a method for preparing ferrous sulfate using hematite slag, comprising:
[0031] S1: a mixture containing hematite slag and concentrated sulfuric acid is contacted with SO2 in a first closed pressure-resistant container to carry out a first reaction to obtain hematite residue and SO2 reduction leaching solution.
[0032] In this step, the main reaction is: SO2 reduces the trivalent iron in the hematite slag to divalent iron ions to obtain ferrous sulfate.
[0033] In some embodiments, the hematite slag may be washed with water before being mixed with concentrated sulfuric acid. Specifically, the hematite slag is mixed with washing and recycling water at a liquid-to-solid ratio of 5 L / kg, and washed with water at 75° C. for 0.5 h. After liquid-solid separation, washed hematite slag is obtained, and the washing liquid is treated and reused.
[0034] Then, the washed hematite slag, concentrated sulfuric acid, the first crystallization liquid and water are mixed and added into a pressure-resistant closed container reactor, heated and SO2 is introduced for reaction, and after sedimentation and separation, the hematite residue and SO2 reduction leaching solution are obtained.
[0035] In some embodiments, the mixture includes the hematite slag, the concentrated sulfuric acid and the first post-crystallization liquid. The hematite slag is the hematite slag produced by removing iron by the hematite method in hydrometallurgy. Based on the total mass of the hematite slag, the mass fraction of iron is greater than 55%, and it also includes components such as Zn, As, and Ca. It can be understood that the mass fraction of Fe is determined by potassium dichromate volumetric method, and the mass fractions of As, Zn, and Ca are determined by inductively coupled plasma atomic emission spectrometry. In this way, the resource utilization of iron in the hydrometallurgy system can be achieved.
[0036] In some embodiments, the SO2 is SO2-containing flue gas generated during the hydrometallurgical zinc smelting process, and the mass concentration of the SO2 exceeds 90%. SO2 has a certain reducing property and can be used as Fe 3+ In the process of hydrometallurgical zinc production, a large amount of cheap and easily available SO2-containing flue gas is often produced, so SO2 is an ideal reducing agent. Compared with iron powder reduction, SO2 is used to reduce Fe 3+ Lower cost. SO2 produced in the process of hydrometallurgy can reduce more than 98% of Fe 3+ Restore is performed to reduce the restoration cost.
[0037] In some embodiments, in the first closed pressure-resistant container, the SO2 partial pressure is 0.15MPa to 0.2MPa (such as 0.15MPa, 0.16MPa, 0.17MPa, 0.18MPa, 0.19MPa or 0.2MPa, etc.), the first reaction time is 2h to 3h (such as 2h, 2.5h or 3h, etc.), and the first reaction temperature is 80°C to 90°C (such as 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, etc.), and the corresponding reaction time and temperature can be controlled according to the raw materials and process requirements. This can make the reaction more complete, which is beneficial to Fe 3+ Reduction to Fe 2+ .
[0038] In some embodiments, the total iron concentration in the SO2 reduction leaching solution does not exceed 140 g / L, for example, it may be 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L or 140 g / L, etc. This is conducive to ensuring the subsequent sedimentation separation.
[0039] S2: subjecting the SO2 reduction leaching solution to a first crystallization to obtain a first solid product containing ferrous sulfate and a first post-crystallization liquid.
[0040] In some embodiments, the first crystallization comprises: cooling the SO2 reduction leachate to 20°C to 30°C (such as 20°C, 25°C or 30°C), stirring and cooling for 3h to 6h (such as 3h, 4h, 5h or 6h), and centrifuging. This can promote the crystallization of ferrous sulfate in the SO2 reduction leachate and improve efficiency.
[0041] In some embodiments, the method for preparing ferrous sulfate using hematite slag further comprises:
[0042] S10: dissolving the first solid product to obtain a first solution.
[0043] Specifically, the first solid product and the second post-crystallization liquid can be heated to 75° C. for redissolution to obtain a redissolved liquid, namely, the first solution.
[0044] In some embodiments, the concentration of TFe (total iron) in the first solution is 130 g / L to 140 g / L (such as 130 g / L, 132 g / L, 134 g / L, 136 g / L, 138 g / L or 140 g / L, etc.), and Fe 3+ The concentration is 1g / L~2.5g / L (such as 1g / L, 1.5g / L, 2g / L or 2.5g / L, etc.).
[0045] In some embodiments, the first solution includes the first solid product and the second post-crystallization liquid, thereby allowing the second post-crystallization liquid to be recycled and improved in utilization rate.
[0046] S20: contacting the first solution with H2S in a second sealed pressure-resistant container to perform a second reaction to obtain a pre-crystallization solution.
[0047] In this step, the unreacted trivalent iron in the first reaction continues to react with H2S and is reduced to divalent iron to obtain a pre-crystallization liquid. The second sealed pressure-resistant container can be the same as the first sealed pressure-resistant container.
[0048] In some embodiments, in the second sealed pressure-resistant container, the H2S partial pressure is 0.01MPa to 0.05MPa (such as 0.01MPa, 0.02MPa, 0.03MPa, 0.04MPa or 0.05MPa, etc.), the reaction time is 0.5h to 1h (such as 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h, etc.), and the reaction temperature is 70°C to 75°C (such as 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, etc.). This is conducive to the reduction of Fe 3+ and precipitate heavy metals to improve reaction efficiency.
[0049] S30: subjecting the pre-crystallization liquid to a second crystallization to obtain a second solid product containing ferrous sulfate and a second post-crystallization liquid.
[0050] In some embodiments, the second crystallization comprises: cooling the pre-crystallization solution to 20-30°C (such as 20°C, 25°C or 30°C), stirring and cooling for 3-6 hours (such as 3 hours, 4 hours, 5 hours or 6 hours), and centrifuging. This can promote the crystallization of ferrous sulfate in the pre-crystallization solution and improve efficiency.
[0051] In some embodiments, the second solid product may also be dried under vacuum conditions or under the protection of a nitrogen atmosphere, wherein the drying temperature does not exceed 40° C., and the drying method may be oven drying or air drying.
[0052] In some embodiments, the second solid product may be ferrous sulfate heptahydrate.
[0053] The following takes the second solid product as ferrous sulfate heptahydrate as an example, Figure 1 , the method for preparing ferrous sulfate from hematite slag of the present application is described in detail, as follows:
[0054] (1) Mixing hematite slag with washing recycling water at a liquid-to-solid ratio of 5 L / kg, washing at 75° C. for 0.5 h, obtaining washed hematite and washing liquid after liquid-solid separation, and recycling the washing liquid after treatment;
[0055] (2) washing hematite, concentrated sulfuric acid, crude crystallization liquid and water are mixed and added into a pressure-resistant closed container, heated and SO2 is introduced to react, and hematite residue and SO2 reduction leaching solution are obtained after sedimentation and separation;
[0056] (3) cooling the SO2 reduction leaching solution obtained in step (2) to 20°C to 30°C, stirring and cooling for 3h to 6h, and obtaining crude ferrous sulfate after centrifugal separation, and returning the crude crystallized solution to step (2);
[0057] (4) heating the crude ferrous sulfate and the liquid after crystallization to 75° C. to redissolve to obtain a ferrous sulfate solution;
[0058] (5) passing H2S into a ferrous sulfate solution for reaction, and obtaining a pre-crystallization solution after sedimentation and filtration;
[0059] (6) cooling the pre-crystallization liquid to 20° C. to 30° C., stirring and cooling for 3 h to 6 h, and centrifuging to obtain the post-crystallization liquid and ferrous sulfate heptahydrate, and returning the post-crystallization liquid to step (4);
[0060] (7) The ferrous sulfate heptahydrate is air-dried to obtain ferrous sulfate, an industrial water treatment agent.
[0061] The embodiments of the present application are described in detail below.
[0062] Example 1
[0063] A wet zinc smelting plant produces hematite slag, and the mass fractions of the components are as follows: Fe-58%, Zn-0.3%, As-0.07%, Ca-2.03%. 1000g of hematite slag was mixed with 5L of water and washed at 75℃ for 30min. After filtering, washed hematite slag and washing liquid were obtained; the washed hematite slag was mixed with concentrated sulfuric acid and water and reduced leached for 2.5h at 90℃ and SO2 partial pressure of 0.2MPa. After sedimentation and filtration, 3.45L of reduced leaching liquid was obtained. The reduced leaching liquid contained 130.8g / L of iron, of which Fe 2+ The concentration is 109.3 g / L (Fe 2+ The concentration was determined by potassium dichromate titration), and after cooling to 25°C, 1238 g of crude crystals and 2680 ml of crude crystal liquid were obtained. The crude crystals were dissolved in water at 75°C to obtain a TFe concentration of 130 g / L, and Fe 3+ A 2.3 g / L ferrous sulfate solution was prepared by introducing H2S at a partial pressure of 0.05 MPa at 75°C for 0.5 h. The pre-crystallization liquid was obtained after sedimentation and filtration. The pre-crystallization liquid was cooled to 30°C to obtain 101.4 g of ferrous sulfate crystals, which were dried under nitrogen atmosphere to obtain ferrous sulfate.
[0064] Example 2
[0065] A wet zinc smelting plant produces hematite slag, and the mass fractions of each component are as follows: Fe-60%, Zn-0.2%, As-0.03%, Ca-1.91%. 400g of hematite slag and 2L of washing liquid recycling water were washed at 75℃ for 30min, and filtered to obtain washed hematite slag and washing liquid; the washed hematite slag was mixed with concentrated sulfuric acid, water, and crude crystallized liquid, and then reduced and leached for 2.5h at 90℃ and SO2 partial pressure of 0.2MPa. After sedimentation and filtration, 3.37L of reduced leaching liquid was obtained, and the reduced leaching liquid contained 133.8g / L of iron, of which Fe 2+ The concentration is 111.7 g / L (Fe 2+ The concentration was determined by potassium dichromate titration), and after cooling to 25°C, 1230 g of crude crystals and 2630 ml of crude crystallization liquid were obtained. The crude crystals and the crystallization liquid were dissolved at 75°C to obtain a TFe concentration of 131.3 g / L, and Fe 3+ A 1.09 g / L ferrous sulfate solution is introduced with H2S. The reaction is carried out at 75°C for 40 min under the condition of H2S partial pressure of 0.05 MPa. The pre-crystallization liquid is then filtered and the pre-crystallization liquid is cooled to 28°C to obtain ferrous sulfate crystals. The crystals are dried under nitrogen atmosphere to obtain ferrous sulfate.
[0066] The ferrous sulfate obtained in the above example was subjected to component analysis. The test results are shown in Table 2, which meet the Class I standard in the water treatment agent standard (GB / T 10531-2016).
[0067] Table 1 Water treatment agent ferrous sulfate standard
[0068]
[0069] Table 2 Test results
[0070] Example 1 Example 2 <![CDATA[Ferrous sulfate (FeSO4·7H2O) / %]]> 91.4 92.1 <![CDATA[Titanium Dioxide (TiO2) / %]]> 0.2 0.15 Insoluble matter / % 0.41 0.35 <![CDATA[Free acid (calculated as H2SO4) / %]]> 0.5 0.3 Arsenic (As) / % 0.0001 0.0001 Lead (Pb) / % 0.0001 0.0002 Cadmium (Cd) / % 0.0001 0.0002 Mercury (Hg) / % 0.00001 0.00001 Chromium (Cr) / % 0.001 0.001
[0071] In the description of the present application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0072] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0073] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing ferrous sulfate from hematite slag, characterized in that: include: contacting a mixture containing hematite slag and concentrated sulfuric acid with SO2 in a first sealed pressure-resistant container for a first reaction to obtain hematite residue and SO2 reduction leaching solution; The SO2 reduction leaching solution is subjected to a first crystallization to obtain a first solid product containing ferrous sulfate and a first post-crystallization liquid.
2. The method according to claim 1, characterized in that The mixture includes the hematite slag, the concentrated sulfuric acid and the first post-crystallization liquid.
3. The method according to claim 1, characterized in that The hematite slag is hematite slag produced by removing iron by a hematite method in hydrometallurgy of zinc, and the mass percentage of iron based on the total mass of the hematite slag is greater than 55%; and / or The SO2 is SO2-containing flue gas generated in the hydrometallurgical zinc smelting process, and the mass concentration of the SO2 exceeds 90%.
4. The method according to claim 1, characterized in that In the first sealed pressure-resistant container, the SO2 partial pressure is 0.15MPa to 0.2MPa, the first reaction time is 2h to 3h, and the first reaction temperature is 80°C to 90°C.
5. The method according to claim 1, characterized in that The total iron concentration in the SO2 reduction leaching solution does not exceed 140 g / L.
6. The method according to claim 1, characterized in that The first crystallization comprises: cooling the SO2 reduction leaching solution to 20°C to 30°C, stirring and cooling for 3h to 6h, and centrifuging.
7. The method according to claim 1, characterized in that Also includes: dissolving the first solid product to obtain a first solution; contacting the first solution with H2S in a second sealed pressure-resistant container to perform a second reaction to obtain a pre-crystallization solution; The pre-crystallization liquid is subjected to a second crystallization to obtain a second solid product containing ferrous sulfate and a second post-crystallization liquid.
8. The method according to claim 7, characterized in that The total iron concentration in the first solution is 130 g / L to 140 g / L, Fe 3+ Concentration of 1g / L to 2.5g / L; and / or The first solution includes the first solid product and the second post-crystallization liquid.
9. The method according to claim 7, characterized in that: In the second sealed pressure-resistant container, the H2S partial pressure is 0.01 MPa to 0.05 MPa, the second reaction time is 0.5 h to 1 h, and the second reaction temperature is 70° C. to 75° C.; and / or The second crystallization comprises: cooling the pre-crystallization liquid to 20°C to 30°C, stirring and cooling for 3h to 6h, and centrifuging.
10. The method according to claim 7, characterized in that The second solid product can also be dried under vacuum conditions or under the protection of a nitrogen atmosphere, wherein the drying temperature does not exceed 40°C.
